2019
DOI: 10.1093/sleep/zsz218
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI of arousals in nonrapid eye movement sleep

Abstract: Arousals commonly occur during human sleep and have been associated with several sleep disorders. Arousals are characterized as an abrupt electroencephalography (EEG) frequency change to higher frequencies during sleep. However, the human brain regions involved in arousal are not yet clear. Simultaneous EEG and functional magnetic resonance imaging (fMRI) data were recorded during the early portion of the sleep period in healthy young adults. Arousals were identified based on the EEG data, and fMRI signal chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
6
18
0
Order By: Relevance
“…After falling asleep, the thalamocortical connectivity for the patients with insomnia disorder was lower (more negative) than that of the healthy controls. We previously found activation in the thalamus and deactivation in the temporal, occipital and frontal gyri during spontaneous arousals in NREM sleep (Zou et al, 2020). In addition, activation in the thalamus and deactivation in cortical regions have been found in studies using auditory and median-nerve stimuli during sleep (Czisch et al, 2004;Del Felice, Formaggio, Storti, Fiaschi, & Manganotti, 2012).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…After falling asleep, the thalamocortical connectivity for the patients with insomnia disorder was lower (more negative) than that of the healthy controls. We previously found activation in the thalamus and deactivation in the temporal, occipital and frontal gyri during spontaneous arousals in NREM sleep (Zou et al, 2020). In addition, activation in the thalamus and deactivation in cortical regions have been found in studies using auditory and median-nerve stimuli during sleep (Czisch et al, 2004;Del Felice, Formaggio, Storti, Fiaschi, & Manganotti, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…The thalamus is a major part of the ascending reticular activating system (Moruzzi & Magoun, 1949). Thalamic activity has been closely related to the transition from NREM sleep to wakefulness, arousals during NREM sleep, recovery from anesthesia, and vigilance level (Balkin et al, 2002; Falahpour, Chang, Wong, & Liu, 2018; Langsjo et al, 2012; Zou et al, 2020). Severe atrophy of the medial dorsal and anterior thalamus was reported in patients with familiar fatal insomnia (Cracco, Appleby, & Gambetti, 2018; Lugaresi et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Oddly enough, the origin of spontaneous arousals remains elusive. Recent fMRI data showed that subcortical regions (including the thalamus, midbrain, basal ganglia and cerebellum) were activated during non-REM (NREM) arousals while cortical regions were deactivated 28 . A recent yet-to-be-reviewed study in rodents provides evidence that arousals leading to sleep state transition are, at least partly driven by the locus coeruleus (LC), brainstem source of norepinephrine with strong and ubiquitous in uence on distant cortical brain regions, including during sleep 29 .…”
Section: Discussionmentioning
confidence: 99%
“…This was further re ected in main effects of EMG status (F 1,989.9 =75.97, p = 0.0001, R² β* =0.07) and transition (F 1,708.6 =39.17, p < 0.0001, R² β* =0.05), as well as in interactions between transition and frequency band (F 2,709.5 =34.62, p < 0.0001, R² β* =0.09), between EMG status and frequency band (F 2,979,2 =187.39, p < 0.0001, R² β* =0. 28), and between EMG status and transition (F 1,879.3 =22.55, p < 0.0001, R² β* =0.025). Based on this rst analysis, we therefore concluded that the factors of arousal heterogeneity eloquently de ne 4 types of arousals (T + E+, T + E-, T-E+, T-E-).…”
Section: Eeg Oscillations Differ Across Arousal Typesmentioning
confidence: 93%
“…In addition, the mechanisms and neuroanatomical substrates of the arousal process during sleep are still matter of debate [48]. The arousal process in sleep has been physiologically considered to have a duplex opposite nature: preserving sleep continuity and ensuring a prompt response to a perturbing stimulus [49][50][51]. In mice, ventromedial thalamic nuclei projecting diffusely to the entire cerebral cortex promotes arousals from NREM sleep [47].…”
Section: Sleep Disruption: Disorders Of Arousalmentioning
confidence: 99%